2014
DOI: 10.1016/j.enbuild.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the thermal resistance and effective thermal mass of a wall using frequent temperature and heat flux measurements

Abstract: a b s t r a c tEvaluating how much heat is lost through external walls is a key requirement for building energy simulators and is necessary for quality assurance and successful decision making in policy making and building design, construction and refurbishment. Heat loss can be estimated using the temperature differences between the inside and outside air and an estimate of the thermal transmittance (U-value) of the wall. Unfortunately the actual U-value may be different from those values obtained using assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 12 publications
(23 reference statements)
0
91
0
1
Order By: Relevance
“…These models were used to predict the time series of interest (i.e., either the heat flux through the structure or the temperatures on opposite sides) and evaluate the thermophysical properties of the element by means of Bayesian inference (Section 2.3) [6,29,30]. Note that in this paper, the term "predict" is used in its statistical meaning of estimating the value of a random variable rather than as a synonym of forecast, which implies making a prediction of the value of the variable at a given time in the future.…”
Section: Dynamic Model: Lumped-thermal-mass Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…These models were used to predict the time series of interest (i.e., either the heat flux through the structure or the temperatures on opposite sides) and evaluate the thermophysical properties of the element by means of Bayesian inference (Section 2.3) [6,29,30]. Note that in this paper, the term "predict" is used in its statistical meaning of estimating the value of a random variable rather than as a synonym of forecast, which implies making a prediction of the value of the variable at a given time in the future.…”
Section: Dynamic Model: Lumped-thermal-mass Modelsmentioning
confidence: 99%
“…Lumped-thermal-mass models including between zero and four effective thermal masses-both with and without the explicit incorporation of solar radiation-were developed in this research (refer to [6] for a pure resistive model, to [29] for a model including two effective thermal masses and four thermal resistances without the explicit incorporation of solar radiation (i.e., two thermal mass model, 2TM), and to [30] for all other models). These models may provide a better description of the thermal structure of the building element, such as in the case of more complex structures.…”
Section: Dynamic Model: Lumped-thermal-mass Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, P. Biddulph et al [19] have stated how the thermal resistance as well as the effective thermal mass of a wall has been observed with the help of heat flux and temperature measurements. The effect of weather on the U-values was properly examined with the smaller time scale and the considerations related to thermal comfort was made available with the estimation of the effective thermal mass.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The work [22] et al presents the description of in-situ monitoring measurements, using the measurements of temperature and heat flux flows as a more precise measurement of the thermal performance of walls. However, the authors indicated some limitations, as for example the fact that with the use of standard methods, the measurements in winter must be carried out over the time period of two weeks.…”
Section: Introductionmentioning
confidence: 99%